O gênero relatório de experimento em contexto de ensino de ciências em cursos técnicos de nível médio - Lea Dutra Costa (2015)
The production of reports after conducting laboratory practice in technical secondary school courses (experiment reports) asks students to produce a genre, strongly regulated, which circulates in more public places.this fact aroused the interest in researching the genre report in the context of teaching young adolescents. This thesis initially conceived up the report as somewhat secondary genre related to the expression of individuality and quite stable (Bakhtin 2003), which challenges its adoption as a mediating learning tool. Thus, the general objective of this thesis is to understand the use and operation of this type of genre. The specific objectives are: to determine which conception of genre guides its adoption as a teaching tool, to identify as well as to discuss the general characteristics that influence its use. Considering the multiple factors involved in learning, we adopted a qualitative methodology, which can not and should not make any generalizations. In the case of this thesis, by themes related to the use of genre as "a major global organizer", "a stabilized configuration of various semiotic subsystems," a learning mega instrument, which enables effective action in defined communication situations, if properly appropriate ( SCHNEUWLY:2004). The corpus of the research consisted of interviews with teachers of four disciplines (two of the basic core and two vocational) and students of the first year of a technical school that requires knowledge in natural sciences and mathematics. Notes about the laboratory practice and the production of reports were taken. The first two reports and the latest report produced by five students of a single discipline in the first academic quarter of 2014 were collected. In the production of the first, there was no guidance from the teacher. This activity took place on the first day of class. The second was collected in the following class and third at the end of academic quarter. There were teachers interventions in the production of the latter texts. The data generated by these research instruments were analyzed based on the proposal of Christopher and Nascimento (2011). According to them, the text is the end product of a process of embodied language in oral and written texts that occurs in a sociological level, where there are parameters for the establishment of a guidance basis for the adoption of a genre model appropriate to the situation. On another level, the psychological one, textualization operations occur. Essentially, this proposal was built according to a socio-discursive interactionist theoretical perspective, with emphasis on the ideas of Bronckart (2003) and Schneuwly and dolz (2004). Following these theorists, are Baltar (2004), Marcuschi (2011), Antunes (2010), Bawarshi and Reiff (2013) among others. It was concluded that, on the sociological level, there were weaknesses on the guidance for the adoption of the report in the context of teaching science related to the concept of genre and its role in technical training. On the psychological level, the biggest obstacles to the use of report originated in the enunciative anchoring of autonomy and in the planning of the types of sequences that make up the sections introduction and conclusion. These sections stopped being produced by the students, without, in the teacher's perspective, compromising teaching and learning, at least in relation to the grade attributed to this last report. As for the linguistic and discursive operations, the analysis indicated that the use of modalizers started decreasing until disappearing from the text, whilst the use of the passive voice and the first person plural in present simple started increasing. therefore, it can be said that the effectiveness of genre as a (mega) instrument depends not only on discursive competence of the student but also on the teachers view on the student writing production not as a text only, but as a genre.